University audiovisual narratives in health communication: The short film Overwhelmed as a vehicle for preventing youth suicidal behavior - Martín Martín, Penélope; Sánchez Gómez, Fernando; Lobillo Mora, Gema (Revista Española de Comunicación en Salud, 2026)
Introduction: Mental health and suicidal behaviour in young people represent a growing challenge that requires effective and sensitive prevention strategies. Audiovisual resources offer significant capability for enhancing awareness and facilitating education in this domain. Objectives: The present study will analyse the university short film Overwhelmed as a health communication tool aimed at preventing suicidal behaviour in young people, evaluating its ability to raise awareness, destigmatise and promote socio-communicative action. Methodology: The present study adopts a research design, the case study, which uses fundamentally qualitative methods, oriented to systematically document and analyse the communicative and formative process of the short film Overwhelmed, with the purpose of evaluating its potential as a tool for raising awareness in mental health and as a replicable model of university-community collaboration. Results: A transdisciplinary collaboration, a sensitive narrative, and a screening of the short film in a high-visibility cultural context reinforced its legitimacy as an educational resource, hereby facilitating the understanding of the messages, identification with the protagonists, and reflection on mental health. Conclusion: University short films have been identified as an effective health communication strategy, combining emotional impact, ethical rigour, and educational relevance, especially when designed through collaborative processes with a focus on prevention.